The Role of Bank BRI's BRILink Digital Services to MSME Business Development in Palembang Using the UTAUT Approach - Agus, Wiranto; Tri Basuki, Kurniawan; Misinem, . (INTI International University, 2023)
The BRILink application for the BRI Bank Palembang office is a Mini ATM service provided by Bank BRI for MSME businesses in Palembang. In its implementation, the BRILink application has never evaluated whether the system created follows user expectations or vice versa. This evaluation needs to be done to find out, pay attention and determine the next steps necessary for the developer to develop a better BRILink application according to user needs. This research was conducted using the UTAUT approach and quantitative methods by distributing questionnaires, validity testing, reliability testing, descriptive testing, and normality testing. Other methods, such as multi-collinearity, heteroscedasticity, auto-correlation, partial correlation, coefficient of determination, simultaneous significance, and individual parameter significance, also apply. The results showed three (3) variables that proved to be partially clear performance expectations, social influence, and facility conditions. Only one variable had no effect, namely the business expectation variable. And all variables simultaneously influence the interest in using the BRILink application.